2010
DOI: 10.1121/1.3484230
|View full text |Cite
|
Sign up to set email alerts
|

Radiated signal characteristics of marine vessels in the cepstral domain for shallow underwater channel

Abstract: This work examines the distribution of cepstral energy of the radiated signal of a marine vessel and the underwater channel modeled as a block-adaptive linear system. Detailed simulation analysis of the signal at the receiver of a passive sonar has led to the observation that, in the cepstral domain the radiated signal of a marine vessel largely occupies the lower cepstral indices while the underwater channel occupies the higher indices, such that for several range and depth conditions, the two can be separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A simulation study on synthetic data has shown that the source signal cepstrum and the channel response cepstrum largely segregate towards the lower and higher cepstrum indices, respectively [32]. It is shown that the signal and the channel appear largely in non-overlapping regions of the cepstrum for shallow underwater channels.…”
Section: Cepstrum-based Featuresmentioning
confidence: 98%
See 3 more Smart Citations
“…A simulation study on synthetic data has shown that the source signal cepstrum and the channel response cepstrum largely segregate towards the lower and higher cepstrum indices, respectively [32]. It is shown that the signal and the channel appear largely in non-overlapping regions of the cepstrum for shallow underwater channels.…”
Section: Cepstrum-based Featuresmentioning
confidence: 98%
“…It is also demonstrated that for a range up to 4000 m and depth of 100 m, cepstral liftering is able to significantly reduce the underwater channel distortions on the radiated noise of marine vessels for this purpose. The mathematical derivation for the channel compensation technique in the cepstrum domain is also presented [32].…”
Section: Cepstrum-based Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this section proposes the use of cepstral features, including mean cepstral features and cepstral liftering features, to make a valid data set. The channel response cepstrum and the original sound dolphins and whales cepstrum could be separated by higher and lower cepstrum indices, respectively 30 . They are in non-overlapping parts of the liftering cepstrum.…”
Section: Average Cepstral Features and Cepstral Liftering Featuresmentioning
confidence: 99%